6p+2=-7

Simple and best practice solution for 6p+2=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6p+2=-7 equation:



6p+2=-7
We move all terms to the left:
6p+2-(-7)=0
We add all the numbers together, and all the variables
6p+9=0
We move all terms containing p to the left, all other terms to the right
6p=-9
p=-9/6
p=-1+1/2

See similar equations:

| 3(2/3)x=2/9 | | -3x+3(4x-5)=213 | | (13x-19)=(9x+25) | | 90+3x+36=180 | | y^2+y^2=65 | | 11=c/15+8 | | 2(3g-5)=-21 | | 3(2/9)x=2/9 | | -14d+4d+19=-11-12d | | k-12=-5 | | 37m+24=-20+26m | | 3x+4x+5x=x+2x+2 | | P^2-6p+3=-4p^2 | | 59x+1261x-45=33(40x+40) | | -3/5w=8 | | 5x-12=11x | | 7-9u-7u=-9-8u | | 5/6f=4 | | -2.4=y+17 | | 12-2(x+3)=4(x-6)-(x-1) | | 9+(x/5)=6 | | -2×+(-8)=2x+8 | | -14p-17=15p | | y=0.6-12 | | 100=15t | | 35=21(x+1)-3(7x-1) | | 13h-19h+18=-9h-18 | | 5a^{2}=51 | | 8h+11(h-5)=-11(3h-5) | | -8s=−8s=1616 | | 21(x+1)-3(7x-1)=35 | | 3a-24=28 |

Equations solver categories